(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
Computational Thinking (CT) ability is increasingly recognized as an essential skill in the digital era, even since the elementary school level. This study aims to explore the effectiveness of an algorithm practice-based approach in everyday life to train the CT abilities of elementary school students. The research method used involves a qualitative descriptive approach by observing groups of students who are given contextual algorithmic activities, such as compiling step-by-step instructions in daily activities. The results of the study indicate that this method is able to significantly improve students’ logical thinking, problem-solving, and information organization skills. In addition, this approach also provides a more enjoyable and relevant learning experience for students. Thus, this paper contributes to the development of CT learning strategies at the elementary school level and emphasizes the importance of integrating algorithm concepts into the elementary education curriculum.